Investigation of Characteristics Whey Protein Isolate/Chitosan with Silica Addition in Biocomposite Film - Ika Zuwanna; Medyan Riza; Sri Aprilia; Yanna Syamsuddin; Syahiddin Said; Rozanna Dewi (International Journal of Technology)
Biocomposites made from whey protein isolate (WPI), chitosan, and silica (SiO2) have the potential as an environmentally friendly biopolymer material. In this research, the WPI biocomposite film has been developed by casting method with the addition of chitosan and SiO2. The loading of SiO2 (1, 3, and 5 %w/w) and chitosan (1.5 %w/w) affects the characteristics of the biocomposite film. The functional groups, morphology, structure, mechanical, thermal, and transparency of the biocomposite films were evaluated by Fourier transform infrared (FTIR) spectroscopy, Scanning electron microscope (SEM), X-ray diffraction (XRD), tensile strength, thermogravimetric (TGA), differential scanning calorimetry (DSC), thickness, swelling, and UV-Vis. The results showed that the swelling value of WPI/chitosan 78.23% decreased to 69.35% with the use of 5% SiO2. Film transparency decreased with higher SiO2, while the film tensile strength increased with the addition of 5% SiO2 with a value of 28.83 MPa. The incorporation of SiO2 improves the thermal properties of biocomposite films. According to the results, increasing the amount of SiO2 in biocomposite films boosts their performance, suggesting that they could eventually replace synthetic polymers in packaging applications.